TOBACCO COLLEGE ACCIDENTAL FIRE ISSUE (Tufts Archival Research Center, 2007)
Overview of the Tobacco College project for the accidental fire issue. Includes pitch and other information about the Tobacco Institute fire program. Examines the self-extinguishing cigarette issue. Discusses interaction with fire service officials.